2018
DOI: 10.1016/j.biocontrol.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dispersal patterns of Diachasmimorpha longicaudata (Hymenoptera: Braconidae) reared on Ceratitis capitata and Anastrepha fraterculus (Diptera: Tephritidae)

Abstract: The dispersal and parasitism abilities of Diachasmimorpha longicaudata, reared on the larval hosts Ceratitis capitata and Anastrepha fraterculus, were evaluated in a guava orchard. Eleven releases of approximately 3000 parasitoids were conducted in a 15-ha orchard and wasp dispersal was monitored from 6 to 272 m away from a central release point. At each monitoring point, larvae of C. capitata and A. fraterculus were offered as hosts for the parasitoids. In five releases, parasitoids were offered only one host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…Fewer obstacles (vegetation) in the release line may have favored the displacement of insects in this direction. A fact also observed by Camargos et al (2018) for D. longicaudata after release in guava.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Fewer obstacles (vegetation) in the release line may have favored the displacement of insects in this direction. A fact also observed by Camargos et al (2018) for D. longicaudata after release in guava.…”
Section: Discussionsupporting
confidence: 78%
“…However, Harbi et al (2015) observed that D. longicaudata released in citrus orchards was able to parasitize C. capitata larvae up to 75 m from the release point. In a guava orchard, D. longicaudata caused parasitism in A. fraterculus and C. capitata larvae located at a distance of 220 m from the release point (Camargos et al 2018). However, in the same study, the highest rate of parasitism (90% of larvae) of A. fraterculus was observed within a radius of up to 22.2 m from the release point, reducing dramatically as the distance increased.…”
Section: Discussionmentioning
confidence: 99%
“…All augmentative studies with successful evidence were performed using parasitoids. These publications involved mass releases to control fruit fly species, including P. concolor against B. oleae in Turkey (Hepdurgun et al 2009) and California, USA (Yokoyama et al, 2008), D. longicaudata against A. suspensa (Sivinski et al, 1996) in Florida, USA, against A. ludens and A. obliqua in Mexico (Montoya et al, 2000(Montoya et al, , 2017, against C. capitata in Guatemala (Cancino et al, 2019), against C. capitata in Argentina (Sánchez et al, 2016), and against C. capitata and A. fraterculus in Brazil (Camargos et al, 2018).…”
Section: Scopes Adopted In Fruit Fly Biocontrol Researchmentioning
confidence: 99%
“…In Brazil, it was introduced in 1994 by "Embrapa Mandioca e Fruticultura" (Carvalho et al 1995) and is present in 10 states. Some studies on D. longicaudata, such as the olfactory response (Silva et al 2007), field dispersal, rates of parasitism and field survival when reared in two hosts (Camargos et al, 2016(Camargos et al, , 2018, and learning behavior of the female related to two essential oils (Zadra et al 2018) have been conducted in Brazil. D. longicaudata has recently been certified as a biological insecticide in Brazil, as it was published in the Federal Register, on September 3, 2018, edition 170, section 1, p. 127, based on Joint Normative Instruction nr.…”
Section: Subfamily Opiinaementioning
confidence: 99%